EPCO-15. SPATIAL-TRANSCRIPTOMICS REVEALS UNIQUE MOLECULAR FEATURES OF FLUORESCENCE-SORTED 5-AMINOLEVULINIC ACID+ INFILTRATIVE TUMOR CELLS ASSOCIATED WITH RECURRENCE AND POOR SURVIVAL IN GLIOBLASTOMA. (12th November 2021) - Andrieux, Geoffroy; Das, Tonmoy; Smith, Stuart; Rahman, Ruman; Chakraborty, Sajib
Abstract: Spatiotemporal heterogeneity of glioblastoma (GBM) originating from genomic and transcriptional variation in spatially distinct sites, may contribute to subtype switching in GBM prior to and upon recurrence. Fluorescence-guided neurosurgical resection utilizing 5-aminolevulinic acid (5ALA) has enabled the isolation of infiltrative margin tumor cells (5ALA+ cells) from a background of non-neoplastic cells. To falsify the hypothesis that the 5ALA+ subpopulation(s) is defined by a unique cellular state, we have explored the spatial-transcriptomic (ST) landscape to interrogate molecular signatures unique to infiltrating 5ALA+ cells in comparison to GBM core, rim, and invasive margin non-neoplastic cells. ST analysis reveals that GBM molecular subtype plasticity is not restricted to recurrence, but manifests regionally in a cell-type-specific manner. Whilst GBM core and rim are highly enriched with Classical and Proneural subtypes, 5ALA+ cells are uniquely enriched with the Mesenchymal subtype (MES). Upregulation of the wound response pathway in 5ALA+ cells implicate hijacking of the wound healing pathway of neural cells to promote tumor growth. Exon-intron split analysis revealed an upregulation of exonic counts for MES and wound-response genes in 5ALA+ cells, implying that these genes are under active post-transcriptional control. Network analysis suggests that wound response genes, including chemokine CCL2 that recruits regulatory T-cells and monocytic myeloid-derived suppressor cells, are controlled by an IRF8-mediated transcriptional program in 5ALA+ cells. A higher stemness signature both in 5ALA+ cells and non-neoplastic cells of the invasive margin emphasizes the role of this microenvironment in stemness acquisition and defines 5ALA+ cells as a rare sub-population of GBM stem cells. Finally, we establish a link between the unique molecular-signatures of 5ALA+ cells, and poor survival and GBM recurrence. Characterization of the 5ALA+ infiltrative sub-population offers an opportunity to develop more effective GBM treatments and urges focus away from the GBM proliferative core, upon which failed targeted therapies have been predicated.